PEMAKNAAN MAHASISWA TERHADAP PESAN LITERASI KEUANGAN DAN PERAN KELUARGA DALAM FILM HOME SWEET LOAN - Saskia Faiza Salsabila; Nuriyatul Lailiyah (Interaksi Online, 2026)
Limited financial literacy among Indonesian university students is associated with increasing financial pressures faced by young adults. Home Sweet Loan portrays these issues through Kaluna's efforts to own a house while facing her family's financial demands. This study examines how university students interpret representations of financial literacy and family roles in the film. A qualitative approach was employed using Stuart Hall's reception analysis, supported by Berger and Luckmann's Social Construction of Reality, Gerbner's Cultivation Theory, and Fishbein and Ajzen's Theory of Reasoned Action. Data were collected through in-depth interviews with five university students selected through purposive sampling. The findings indicate that three participants occupied the dominant-hegemonic position, while two adopted a negotiated position. Financial literacy was interpreted as the ability to plan finances, prioritize needs, achieve financial independence, and maintain financial transparency within the family. Interpretations of family roles varied according to each participant's background. Home Sweet Loan was understood as a medium that encourages reflection on financial management and family relationships.